2019
DOI: 10.6065/apem.2019.24.3.203
|View full text |Cite
|
Sign up to set email alerts
|

A case of treatment-induced neuropathy in an adolescent with type 1 diabetes

Abstract: Treatment-induced neuropathy (TIN) in diabetes is an acute and painful yet completely reversible small fiber neuropathy precipitated by a rapid improvement in glycemic control. TIN is rare in children. A 16-year-old girl developed symmetrical painful neuropathy of the foot, autonomic neuropathy, and retinopathy 5 weeks after the diagnosis of type 1 diabetes. All causative workups were negative except for a drop-in hemoglobin A1c (HbA1c) from 17.4% to 7%, which fit with a diagnosis of TIN. Following symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In this series we describe 7 cases of TIND in children and young adults treated at 2 pediatric centers, increasing recognition of TIND as a complication of pediatric diabetes. Prior to our report, only 2 pediatric cases had been published [ 4 , 7 ], indicating that the occurrence of TIND is more than the paucity of literature suggests. By raising awareness, we hope to enhance detection and timely management of this distressing and potentially debilitating condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series we describe 7 cases of TIND in children and young adults treated at 2 pediatric centers, increasing recognition of TIND as a complication of pediatric diabetes. Prior to our report, only 2 pediatric cases had been published [ 4 , 7 ], indicating that the occurrence of TIND is more than the paucity of literature suggests. By raising awareness, we hope to enhance detection and timely management of this distressing and potentially debilitating condition.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of TIND are well described in adult literature, and a recent report has shown that 11% of patients (n = 954) referred to a diabetic neuropathy clinic had presentations consistent with TIND [ 3 ]. The prevalence in children remains unclear, as pediatric literature is scarce, with only 2 cases reported [ 4 , 7 ].…”
mentioning
confidence: 99%
“…13 Its prevalence in subjects with diabetes in a third-level reference centre was reported to be 10.9%. 13 Cases reported in the literature 4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] show that the mean age of those affected by TIND is 36.55 years (95% , and that there is a slight male predominance (57.14% vs 42.86%). Type 1 DM was more frequent than type 2 DM (64.29% vs 35.71%), and patients had the disease for a mean of 4.9 years (95% CI 3.17-6.64).…”
Section: Epidemiologymentioning
confidence: 99%

Treatment‐induced neuropathy of diabetes: an update

Quiroz‐Aldave,
Concepción‐Zavaleta,
del Carmen Durand‐Vásquez
et al. 2023
Practical Diabetes
“…DCCT demonstrated that intensive glycemic regulation reduced DN and CAN risk 25,206,207 . On the other hand, there is little evidence that well controlled glycemia improves neuropathic pain in T1D, but rapid and large glycemic drops can occasionally precipitate a dramatic worsening of pain 208,209 . Recently, glucose variability was proposed to accelerate DN development and progression, but well‐designed studies are needed in children and youth 210,211 …”
Section: Managing Dn In Children and Youthmentioning
confidence: 99%